Dizziness and headache in emergency brain MRI: A Retrospective analysis of imaging outcomes - Happonen, Tatu (fi=Turun yliopisto|en=University of Turku|, 2025)
Dizziness and headache may pose diagnostic challenges and are common reasons for emergency neuroimaging. While computed tomography has traditionally been the first-line imaging method for emergency neuroimaging, magnetic resonance imaging (MRI) provides an alternative with high accuracy and without ionizing radiation. This thesis aimed to explore the imaging outcomes of emergency brain MRI in patients presenting with these symptoms and to identify clinical factors predictive of acute imaging findings. This thesis included patients who underwent emergency brain MRI because of acute dizziness, headache, or clinical suspicion of cerebral venous sinus thrombosis (CVST) between April 2014 and January 2019 in Turku University Hospital, an academic tertiary care referral center. Patient characteristics, relevant clinical data, and imaging outcomes were recorded and analyzed. Among the 1,169 patients imaged for dizziness, acute stroke was found in 17%, and other clinically significant pathology in 8% of patients. Older age, male sex, and a prevalence of cardiovascular risk factors and neurologic signs were predictive of acute stroke. Stroke was observed in 14% of patients presenting with dizziness as their sole symptom. Of the 696 patients with headache, 20% had clinically meaningful findings, and a similar proportion presented incidental findings of little clinical relevance. Older age, smoking, nausea, and signs/symptoms of infection were associated with significant findings, whereas patients with numbness or history of migraine had less significant findings. Among the 327 patients imaged for suspected CVST, a low rate of CVST (1.5%) was observed, with 15% exhibiting other clinically significant pathology. Predictors of acute pathology may aid in prioritizing patients for emergency MRI. This thesis demonstrates the current diagnostic yields of emergency brain MRI and contributes to optimizing the clinical impact of emergency neuroimaging.

Huimauksen ja päänsäryn päivystyksellinen aivojen magneettikuvaus: Kuvantamislöydösten retrospektiivinen analyysi Huimaus ja päänsärky voivat aiheuttaa diagnostisia pulmatilanteita, ja ne ovat yleisiä syitä päivystykselliselle neurokuvantamiselle. Tietokonetomografia on perinteisesti ollut ensisijainen päivystyksellisen neurokuvantamisen menetelmä, jolle magneettikuvaus (MRI) tarjoaa tarkan vaihtoehdon ilman ionisoivaa säteilyä. Tämän väitöskirjatutkimuksen tarkoituksena oli tutkia päivystyksellisen aivojen MRI:n kuvantamislöydöksiä huimaus- ja päänsärkypotilailla, sekä selvittää kliinisiä tekijöitä, jotka ennustavat akuutteja kuvantamislöydöksiä. Tutkimukseen sisällytettiin akuutin huimauksen, päänsäryn tai kliinisen sinustromboosiepäilyn vuoksi päivystysluonteisesti aivojen MRI:lla kuvatut potilaat, huhtikuun 2014 ja tammikuun 2019 välillä Turun yliopistollisessa keskussairaalassa. Kartoitimme ja analysoimme potilaiden olennaiset kliiniset tiedot, sekä kuvantamislöydökset. 1 169:stä huimauksen vuoksi kuvatusta potilaasta 17 %:lla todettiin akuutti aivoinfarkti ja 8 %:lla jokin muu kliinisesti merkittävä kuvantamislöydös. Korkea ikä, miessukupuoli, sydän- ja verisuonitautien riskitekijät, sekä neurologiset oireet ennustivat akuuttia aivoinfarktia. Potilaista, joilla huimaus oli ainoa oire, 14 %:lla todettiin aivoinfarkti. 696:sta päänsäryn vuoksi kuvatusta potilaasta 20 %:lla oli kliinisesti merkittävä kuvantamislöydös, ja vähämerkityksellisiä sattumalöydöksiä todettiin samassa suhteessa. Korkea ikä, tupakointi, pahoinvointi ja infektio-oireet olivat yhteydessä merkittäviin kuvantamislöydöksiin, kun taas puutumisoireen tai migreenihistorian omaavilla potilailla merkittäviä löydöksiä todettiin vähemmän. 327:n potilaan joukosta, joilla epäiltiin sinustromboosia, vain 1,5 %:lla todettiin sinustromboosi ja 15 %:lla muita kliinisesti merkittäviä löydöksiä. Akuuttien kuvantamislöydösten ennustetekijät voivat auttaa päivystyksellisten MRI-tutkimusten potilasvalinnassa. Väitöskirjatutkimus osoittaa päivystyksellisen aivojen magneettikuvauksen ajankohtaista diagnostista arvoa ja edistää täten päivystyksellisen neurokuvantamisen kliinisen arvon optimointia.